FcγRI FG-loop functions as a pH sensitive switch for IgG binding and release - Lu, Jinghua; Spencer, Matthew; Zou, Zhongcheng; Traver, Maria; Brzostowski, Joseph; Sun, Peter D. (Frontiers in Immunology, 2023)
Understanding the molecular mechanism underlying the hierarchic binding between FcγRs and IgG antibodies is critical for therapeutic antibody engineering and FcγR functions. The recent determination of crystal structures of FcγRI-Fc complexes, however, resulted in two controversial mechanisms for the high affinity receptor binding to IgG. Here, we describe high resolution structures of a bovine FG-loop variant of FcγRI in complex with the Fc fragment of IgG1 crystallized in three different conditions at neutral pH, confirming the characteristic FG loop-Fc interaction is critical to the high affinity immunoglobulin binding. We showed that the FcγRI D2-domain FG-loop functioned as a pH-sensing switch for IgG binding. Further live cell imaging of FcγRI-mediated internalization of immune complexes showed a pH sensitive temporal-spatial antibody-antigen uptake and release. Taken together, we demonstrate that the structures of FcγRI-Fc crystallized at neutral and acidic pH, respectively, represent the high and low affinity binding states of the receptor for IgG uptake and release. These results support a role for FcγRI in antigen delivery, highlight the importance of Fc glycan in antibody binding to the high affinity receptor and provide new insights to future antibody engineering.